The dynamics of going legitimate and running for barangay politics in Leon, Iloilo - Allones, April Joy G; Fillaro, Geraldine (Miagao, Iloilo University of the Philippines in the Visayas, 2005)
This study explains the process of going back to the mainstream of society of former rebels and their political participation in the barangay politics. Descriptive in nature, it has the following objectives; first is to identify the social climate and political recruitment patterns (reasons, mindset, and community situation) of rebel returnees; second, is to identify the resources from national or local politicians and "partido", who endorsed the rebel returnees; Third to identify the factors behind the success or failure of rebel returnee candidates in barangay elections. The method used in gathering of the data was personal interview with an interview guide., The study found out that in the recruitment, selection and election patterns of individuals, whether a private individual or a rebel returnee, several factors are considered before the people decides who they want to vote. Personality traits kinship ties and political machineries are always important to dominate local or national politics in the Philippines. Motivation and political were also popular reasons for winning the elections. Inspired and influence by the doctrines of the underground movement, the rebel returnees joined the politics due to their strong conviction to effect changes they have been advocating ever since. But, their rebel background had been a setback for their election into public position. They refused endorsement from local partidos for they believe and adhered to their genuine cause of fielding themselves in politics without political backings. Some of these rebel returnees succeeded in their quest for barangay position and some did not. The success and failure of each rebel returnees had been determined by varying factors present in the society.
Thesis (Undergraduate, Bachelor of Arts in Political Science ) -- Miagao, Iloilo : University of the Philippines in the Visayas, March 2005.
Keywords: Rebel Returnees